Vibrating rod VBR-01 - Amirul Iskandar, Amira Elina; Yazi, Farhan Al Faizeen Rozaimi; Mohd, Nur Aisyah; Isiara, Ain Nur Fatihah; Mohamed Faisal, Sharifah Nadia (Pusat Asasi, UiTM Cawangan Dengkil, 2020)
From a person with sight disability point of view, the simplest thing can be deemed as a challenge to them. One of the common everyday acts the unsighted deemed as challenging is crossing the roads. Thus, this innovation is designed to help the visually impaired to cross the roads safely by using their sense of touch instead of only relying on their sense of hearing. For this innovation to serve its purpose, the visually impaired have to hold on to the rod attached to the pole of the traffic light and wait for it to vibrate as a signal to cross the road. The commercial potential of this innovation is that it is user-friendly, reasonably priced and very beneficial to the disabled. In short, this advancement may assist with facilitating their burden to walk across the street more safely without the assistance of anybody.